Present Tree Planting and Management Activities in Four Rural Communities in Leyte Province, the Philippines - Cedamon, Edwin O.; Emtage, Nick F.; Suh, Jungho; Herbohn, John L.; Harrison, Steve R.; Mangaoang, Eduardo O. (Annals of Tropical Research, 2005)
Demand for timber in Leyte Province continues to increase whilst supplies from domestic sources have contracted following suspension of logging in remaining natural forests. One approach to meet the deficit in timber supplies has been to encourage timber planting by smallholders. A survey was undertaken in four rural communities to help assess present tree planting and management activities of households and their tree planting and management intentions. It was found out that not more than 100 trees are managed by each of about 61% of the households who have planted trees. There were 88 different species planted or managed by households, but 83% of the total trees planted belong to only 10 species, including mahogany, ipil-ipil, gmelina and molave. The primary purpose of tree planting is to meet household needs for timber for dwelling construction and fruit production. About 72% of the total trees being managed by households were planted, as distinct from natural regeneration, with planting stock coming mostly from own seeds, nursery and wildings. Only four respondents had registered any of their trees with the Department of Natural Resources and Environment (necessary for commercial harvesting), the main reason for lack of registration appearing to be lack of awareness of this procedure.